Positive Psychology: Looking Back and Looking Forward - Ryff, Carol D. (Frontiers in Psychology, 2022)
Envisioning the future of positive psychology (PP) requires looking at its past. To that end, I first review prior critiques of PP to underscore that certain early problems have persisted over time. I then selectively examine recent research to illustrate progress in certain areas as well as draw attention to recurrent problems. Key among them is use of poorly constructed measures of well-being and reliance on homogeneous, privileged samples in the studies and interventions conducted. Another major concern is the commercialization of PP that points to the need for greater oversight and quality control in profit-seeking endeavors. Looking ahead, I advocate for future science tied to contemporary challenges, particularly ever-widening inequality and the pandemic. Together, these constitute intersecting catastrophes that greatly need scientific attention. Such problems also bring into focus “neglected negatives” that may be fueling such difficulties, including greed and indifference, especially among the privileged, and stupidity. Anger, which defies easy characterization as positive or negative, also warrants greater scientific study. Going forward I advocate for greater study of domains that may nurture good lives and just societies – namely, participation in the arts and encounters with nature. Overall, my entreaty to PP is to reckon with persistent problems from its past, while striving toward a future that is societally relevant and virtuous.